PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD SD INPRES 3 KOTARAYA - Deswati, Elvira; Sugita, Gandung; Mallo, Bakri (Jurnal Kreatif Tadulako Online, 2018)
The topic this research is Improving Students Learning Outcomes on Number Raised to the Third Power through STAD Learning Model at sixth Grade Inpres 3 Kotaraya. Problems has found in this reseach was the lack of student learning outcomes. This research purpose to improve students learning outcomes on number raised to the third power at sixth SD Inpres 3 Kotaraya through cooperative learning STAD type. Type of this research is a classroom action research which cycles, consist of planning, action, observation, and reflection. The data collected in this research consist of student learning result, observation of teacher activities and result from observation of student activities. Result of research in cycle I was obtained who has completed 18 students and has not completed 15 students with presentation of classical absorption is 69,8% and learning classical mastery 54,5%. In cycle II was obtained the improving in complete individually become 28 students, with presentation of classical absorption is 77,4% and learning classical mastery 84,8%. That mean learning in cycle II has been reaching as indicator success with classical absorption minimal 65% and learning classical mastery minimalÂ 75%. Based classical absorption and learning classical mastery in cycle II, so that can be concluded that cooperative learning STAD type at sixth SD Inpres 3 Kotaraya can improve student learning outcomes on number raised to the third power. Keywords : Students learning outcomes, Model Cooperative learning STAD type